Relate North 2024: New Genre Arctic Art Education : Nomadic Hub of New Genre Arctic Art Education in Karasjok, 2024 - Manninen, Annamari; Jokela, Timo; Hiltunen, Mirja; Tuononen, Emilia; Sirkiä, Riitta; Peltonen, Silja; Jalvela, Ante; Korsström-Magga, Korinna; Rylander, Sara; Lundstedt, Lotta; Stiegemeyer, Dylan; Tiselius, Anna; et al. (Lapin yliopisto, 2024)
Installation, video (5 min.), printed photos, and ceramic sculptures. Installation, video (5 min.), printed photos, and ceramic sculptures.